Número: o conceito a partir de jogos - Fonseca, Rogério Ferreira da (2005)
The subject that is presented in this research is the concept of number, in special the approach that was elaborated by the Mathematician John H. Conway. It is very interesting Conway s concept of number in Mathematics Education, because of two complementary aspects of the definition of number, which are: intensional and extensional. The extensionality is expressed by the application of the concept of number to certain games including the Hackenbush game, which is studied in this presentation. We had the purpose of investigate a new approach to the concept of number, looking for elements that would consequently support the teaching learning process. Our investigation has as presupposition that number is one of the fundamental concepts of Mathematics, that its constitution presents a variety of approaches and that none of them gives the possibility of an answer to the question: What is number? As a subsidy to the investigation we evaluate phylosophical answers aboret the nature and existence of numbers, which provide us clues of the complexity implied in this notion. We also present some researches that study the concept of numbers coming from games, as well as, the implication of such studies to the teaching learning process in Mathematics.